Endoscopy-verified occult subependymal dissemination of glioblastoma and brain metastasis undetected by MRI: prognostic significance - Iacoangeli, Maurizio (Dove Medical Press, 2012)
Although various prognostic indices exist for patients with malignant brain tumors, the prognostic significance of the subependymal spread of intracranial tumors is still a matter of debate. In this paper, we report the cases of two intraventricular lesions, a recurrent glioblastoma multiforme (GBM) and a brain metastasis, each successfully treated with a neuroendoscopic approach. Thanks to this minimally invasive approach, we achieved good therapeutic results: we obtained a histological diagnosis; we controlled intracranial hypertension by treating the associated hydrocephalus and, above all, compared with a microsurgical approach, we reduced the risks related to dissection and brain retraction. Moreover, in both cases, neuroendoscopy enabled us to identify an initial, precocious subependymal tumor spreading below the threshold of magnetic resonance imaging (MRI) detection. This finding, undetected in pre-operative MRI scans, was then evident during follow-up neuroimaging studies. In light of these data, a neuroendoscopic approach might play a leading role in better defining the prognosis and optimally tailored management protocols for GBM and brain metastasis.